2012
DOI: 10.1161/circulationaha.112.123117
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk of High- Versus Moderate-Intensity Aerobic Exercise in Coronary Heart Disease Patients

Abstract: Background-Exercise performed at higher relative intensities has been found to elicit a greater increase in aerobic capacity and greater cardioprotective effects than exercise at moderate intensities. An inverse association has also been detected between the relative intensity of physical activity and the risk of developing coronary heart disease, independent of the total volume of physical activity. Despite that higher levels of physical activity are effective in reducing cardiovascular events, it is also adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
260
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(293 citation statements)
references
References 49 publications
(53 reference statements)
10
260
0
14
Order By: Relevance
“…A Swedish study showed a 31% reduced risk for incident MI associated with high versus low leisure‐time physical activities 34. Earlier studies with data on high‐ and moderate‐intensity exercise among CVD patients found that both intensity levels decreased CVD risk, but also pointed to the knowledge gap regarding the right intensity and amount of physical activity in secondary prevention of CVD 35, 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study showed a 31% reduced risk for incident MI associated with high versus low leisure‐time physical activities 34. Earlier studies with data on high‐ and moderate‐intensity exercise among CVD patients found that both intensity levels decreased CVD risk, but also pointed to the knowledge gap regarding the right intensity and amount of physical activity in secondary prevention of CVD 35, 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…The authors, therefore, speculated that the total energy spent on exercise training is more important to increasing peak oxygen uptake than exercise intensity 117. The number of serious adverse events with HIT was low and did not differ from MCT in patients with CAD 116, 118. In patients with heart failure, serious adverse events were numerically higher with HIT than with MCT.…”
Section: Exercise Prescriptionmentioning
confidence: 99%
“…108 In a review of 4846 CHD patients enrolled in interval and continuous CR regimens in Norway, the difference in event rates were 1 in 129,456 hours of moderate ET and 1 in 23,182 hours of high intensity ET. 109 Of such studies, Japan appears to have some of the lowest rates of adverse events, with only 1 life-threatening adverse event occurring in 383,096 patienthours of ET. 110 The most serious CVD complications of structured ET for CVD patients are acute MI and sudden cardiac death, usually from ventricular fibrillation which can be triggered by exercise-induced myocardial ischemia, especially in patients with left ventricular dysfunction.…”
mentioning
confidence: 99%